The mechanism of protriptyline-induced Ca2+ movement and non-Ca2+-triggered cell death in PC3 human prostate cancer cells. (3rd September 2015) - Chang, Hong-Tai; Chou, Chiang-Ting; Yu, Chia-Cheng; Tsai, Jeng-Yu; Sun, Te-Kung; Liang, Wei-Zhe; Lin, Ko-Long; Tseng, Hui-Wen; Kuo, Chun-Chi; Chen, Fu-An; Kuo, Daih-Huang; Pan, Chih-Chuan; et al.
Abstract: Protriptyline, a tricyclic anti-depressant, is used primarily to treat the combination of symptoms of anxiety and depression. However, the effect of protriptyline on prostate caner is unknown. This study examined whether the anti-depressant protriptyline altered Ca 2+ movement and cell viability in PC3 human prostate cancer cells. The Ca 2+ -sensitive fluorescent dye fura-2 was used to measure [Ca 2+ ]i . Protriptyline evoked [Ca 2+ ]i rises concentration-dependently. The response was reduced by removing extracellular Ca 2+ . Protriptyline-evoked Ca 2+ entry was inhibited by store-operated channel inhibitors (nifedipine, econazole and SKF96365), protein kinase C activator (phorbol 12-myristate 13 acetate, PMA) and protein kinase C inhibitor (GF109203X). Treatment with the endoplasmic reticulum Ca 2+ pump inhibitor 2, 5-di-tert-butylhydr-oquinone (BHQ) in Ca 2+ -free medium inhibited 60% of protriptyline-evoked [Ca 2+ ]i rises. Conversely, treatment with protriptyline abolished BHQ-evoked [Ca 2+ ]i rises. Inhibition of phospholipase C with U73122 suppressed 50% of protriptyline-evoked [Ca 2+ ]i rises. At concentrations of 50–70 µM, protriptyline decreased cell viability in a concentration-dependent manner; which were not reversed by chelating cytosolic Ca 2+ with 1, 2-bis(2-aminophenoxy)ethane-N, N, N', N'-tetraacetic acid-acetoxymethyl ester (BAPTA/AM). Collectively, in PC3 cells, protriptyline evoked [Ca 2+ ]i rises by inducing phospholipase C-associated Ca 2+ release from the endoplasmic reticulum and other stores, and Ca 2+ influx via protein kinase C-sensitive store-operated Ca 2+ channels. Protriptyline caused cell death that was independent of [Ca 2+ ]i rises.